Reporting the Fantastic: Deferral and Pan-determinism in Ugo Tarchetti - Reza, M (Oxford University Press, 2017)
This article explores how Ugo Tarchetti balances between the fantastic and the real in his narratives through explicit real-world location together with a deferral of the impossible. I argue that Tarchetti allows the fantastic and the real to coexist by enclosing the fantastic with reassuring markers, deferring its authenticity to lost manuscripts, or for the narrator to simply claim to be passing on a story. Additionally, I make the case that Tarchetti’s use of pan-determinism complements this effect, and that as well as balancing the real with the fantastic, he is also representing the new social reality of the rise of practices such as spiritualism in late nineteenth century Italy.